Prevalence of diastolic dysfunction in Normotensive diabetics below 45 years of age - Dr. Nitesh Sukhwani; Dr. Mohit Jain (International Journal of Medical Research and Review, 2020)
Introduction: Dengue rarely affects the heart but clinical symptoms of cardiac involvement may range greatly from silent illness to severe myocarditis resulting in death. Clinical features are asymptomatic and most are transient among patients with DF/DHF.Material and methods: It was an observational study conducted at the Department of General Medicine, Peoples College of Medical Sciences and Research Centre, Bhopal. The total duration of the study was One and a half years from November 2016 to APR 2018. All normotensive diabetic patients less than 45 years of age presenting to the Department of General Medicine, Peoples College of Medical Sciences and Research Centre, Bhopal during one and half years from which data was collected using as per given proforma.Results: In the present study, It was found that significant Pearson's correlation between age of diabetics and diastolic changes in ECHO, and serum creatinine and diastolic changes in ECHO. The rest of the parameters like blood urea, blood pressure, RBS, FBS, PPBS, and duration of diabetes were not significantly correlated.Conclusion: It was concluded that in the present study, diabetes mellitus is itself a risk factor for developing diastolic dysfunction though its prevalence increases with increasing age, serum creatinine and there is no association found between duration of diabetes and diastolic dysfunction. So screening of every young normotensive diabetic for diastolic dysfunction should be done to prevent early cardiovascular disease.